Personal finance in your 20s for dummies - Tyson, Eric (Eric Kevin) (Hoboken, NJ : Wiley Pub., 2011)
When it comes to protecting your financial future, starting sooner rather than later is the smartest thing you can do. This hands-on guide provides you with the targeted financial advice you need to establish firm financial footing in your 20s and to secure your finances for years to come.
Includes index.
Keywords: Finance, Personal; Young adults -- Finance, Personal